1995
DOI: 10.1007/bf00145154
|View full text |Cite
|
Sign up to set email alerts
|

Oribatid mites: prospects for their use in ecotoxicology

Abstract: Oribatid mites are a group of arthropods that have had remarkable evolutionary success with regard to species richness, variety of habitats colonized, life-cycle variation and reproductive patterns. The aim of this paper is to review some of the important features of Oribatida in relation to the possible use of these animals in ecotoxicological experiments. Their often sedentary way of living, combined with a narrow dependence on microhabitats qualify oribatids as potential indicator organisms for air and soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 41 publications
1
48
1
Order By: Relevance
“…It is known that various soil amendments affect adult Oribatida abundances [66], but until now few studies have analyzed the differences of effects of soil amendments or other deteriorations on juvenile and adult stages. Juvenile stages are more sensitive to changes in soil chemistry and are more suitable to monitor effects of environmental changes [67]. Thus, more attention should be drawn to these stages in future studies.…”
Section: Hypothesis I: Interplay Between Water Availability and Toxicmentioning
confidence: 99%
“…It is known that various soil amendments affect adult Oribatida abundances [66], but until now few studies have analyzed the differences of effects of soil amendments or other deteriorations on juvenile and adult stages. Juvenile stages are more sensitive to changes in soil chemistry and are more suitable to monitor effects of environmental changes [67]. Thus, more attention should be drawn to these stages in future studies.…”
Section: Hypothesis I: Interplay Between Water Availability and Toxicmentioning
confidence: 99%
“…These organisms possess such kind of extraordinary characteristics by which (considered even separately or as a whole) they are able to indicate different changes in their environment. These characteristics have been summarized in several reviews, most thoroughly in the works of Lebrun and van Straalen (1995), Behan-Pelletier (1999) and Gulvik (2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, they consume variuos kinds of food, and as such, they participate in numerous ways in the structure of the food web (Lebrun and van Straalen, 1995). Thus they are in strong interaction with their microenvironment (e. g. Castorage, heavy metal accumulation (Norton and Behan-Pelletier, 1991, Behan-Pelletier on the soil and in the foliage of trees is limited primarily not by physical barriers but e. g. water content.…”
Section: Introductionmentioning
confidence: 99%
“…Although the linkages between Oribatida community structure and soil pH (e.g., Van Straalen et al, 1988;Lebrun and van Straalen, 1995), forest stand age (Zaitev et al, 2002), tree species (Migge et al, 1998;Sylvain and Buddle, 2010), forest type and regional factors (Erdmann et al, 2012), as well as forest type, log type, and regional factors (Bluhm et al, 2015) have been comprehensively studied, the deterministic factors are still poorly understood. In the current study, no causal link between Oribatida assemblage and fruit yield were found, a result that has not previously been described.…”
Section: Trophic Interactions In the Soil Food Web Accounted For Dissmentioning
confidence: 99%